WST11 vascular targeted photodynamic therapy effect monitoring by multispectral optoacoustic tomography (MSOT) in mice - Neuschmelting, Volker; Kim, Kwanghee; Malekzadeh-Najafabadi, Jaber; Jebiwott, Sylvia; Prakash, Jaya; Scherz, Avigdor; Coleman, Jonathan A.; Kircher, Moritz F.; Ntziachristos, Vasilis (Theranostics, 2018)
Objective: Monitoring emerging vascular-targeted photodynamic therapy (VTP) and understanding the time-dynamics of treatment effects remains challenging. We interrogated whether handheld multispectral optoacoustic tomography (MSOT) could noninvasively monitor the effect of VTP using WST11, a vascular-acting photosensitizer, on tumor tissues over time using a renal cell cancer mouse model. We also investigated whether MSOT illumination can induce VTP, to implement a single-modality theranostic approach. Materials and Methods: Eight BalB/c mice were subcutaneously implanted with murine renal adenocarcinoma cells (RENCA) on the flank. Three weeks later VTP was performed (10 min continuous illumination at 753 nm following intravenous infusion) using WST11 or saline as control. Handheld MSOT images were collected prior to VTP administration and subsequently thereafter over the course of the first hour, at 24 and 48 h. Data collected were unmixed for blood oxygen saturation in tissue (SO2) based on the spectral signatures of deoxy- and oxygenated hemoglobin. Changes in oxygen saturation over time, relative to baseline, were examined by paired t-test for statistical significance (p < 0.05). In-vivo findings were corroborated by histological analyses of the tumor tissue. Results: MSOT is shown to prominently resolve changes in oxygen saturation in tumors within the first 20 min post WST11-VTP treatment. Within the first hour post-treatment, SO2 decreased by more than 60% over baseline (p < 0.05), whereas it remained unchanged (p > 0.1) in the sham-treated group. Moreover, unlike in the control group, SO2 in treated tumors further decreased over the course of 24 to 48 h post-treatment, concomitant with the propagation of profound central tumor necrosis present in histological analysis. We further show that pulsed MSOT illumination can activate WST11 as efficiently as the continuous wave irradiation employed for treatment. Conclusion: Handheld MSOT non-invasively monitored WST11-VTP effects based on the SO2 signal and detected blood saturation changes within the first 20 min post-treatment. MSOT may potentially serve as a means for both VTP induction and real-time VTP monitoring in a theranostic approach.
CRIS-Team Scopus Importer:2023-03-08
Keywords: MSOT; Optoacoustic imaging; Photoacoustic imaging; Photodynamic therapy; Renal cell carcinoma; Vascular targeted photodynamic therapy